2022
DOI: 10.1002/hpm.3585
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐evaluation of studies on community physical activity programs in Brazil

Abstract: Background: The use of the meta-evaluation, especially in health promotion programs, is still scarce. Aim: To verify if the evaluation studies conducted about the Academia da Cidade Programme and the Academia da Saúde Programme comply with the principles and standards of the meta-evaluation. Methods: This meta-evaluation study was conducted using articles from scientific databases. The parameters of utility, propriety, and accuracy, as defined by the Joint Committee on Standards for Educational Evaluation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In this study, the prevalence of physical activity for leisure was higher in white adults solely in the years 2010-2011, showing no difference in the years from 2012 to 2019. A possible explanation for the lack of difference observed since 2012 is the implementation of the Health Academy Program in Brazil, by the Ministry of Health, in 2011 39 . Preliminary results from one center of the Health Academy Program in Belo Horizonte showed that most participants of this program were non-white individuals (56.4%) 40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the prevalence of physical activity for leisure was higher in white adults solely in the years 2010-2011, showing no difference in the years from 2012 to 2019. A possible explanation for the lack of difference observed since 2012 is the implementation of the Health Academy Program in Brazil, by the Ministry of Health, in 2011 39 . Preliminary results from one center of the Health Academy Program in Belo Horizonte showed that most participants of this program were non-white individuals (56.4%) 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of the Health Academy Program is to promote health for all the population by implementing gym centers throughout Brazil, with infrastructure, equipment, and professional staff 41 . This program includes physical activity classes in rehabilitated public open spaces in lowincome neighborhoods, health screening and counseling, and many other community-building activities in place-based settings (parks and plazas) 39 . A prior study investigated the impact of the Health Academy Program in 80 cities in the Pernambuco state, assessing 2,370 individuals in 2011, 3,824 individuals in 2012, and 3,835 individuals in 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation